2022
DOI: 10.1055/s-0042-1755353
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Barriers to Nursing Care Quality in Oncology Units

Abstract: Background: Every patient expects safe and quality patient care. A satisfying journey during hospitalization indicates quality care. Nurses provide a significant component of patient care over a long period, compared to any other healthcare professional. This study aims to find patient satisfaction in oncology units and identify the barriers to nursing care quality. Materials and Methods: A cross-sectional correlation design was used with 100 cancer patients admitted to oncology units of tertiary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this research, more than two thirds of the respondents were married and more than three quarters of them were rural residents. Our finding was enhanced by (16) in their study titled "Patient satisfaction and barriers to nursing care quality in oncology units" and showed that less than two thirds of the participants were married. While, this result was dissimilar to (17) in their study titled "Patients' perceptions of the quality of nursing services" and mentioned that more than fifty percent of the participants lived in rural areas.…”
Section: Mohamed Ng Nursing Servicesmentioning
confidence: 50%
“…In this research, more than two thirds of the respondents were married and more than three quarters of them were rural residents. Our finding was enhanced by (16) in their study titled "Patient satisfaction and barriers to nursing care quality in oncology units" and showed that less than two thirds of the participants were married. While, this result was dissimilar to (17) in their study titled "Patients' perceptions of the quality of nursing services" and mentioned that more than fifty percent of the participants lived in rural areas.…”
Section: Mohamed Ng Nursing Servicesmentioning
confidence: 50%
“…The Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) has been validated in several countries [8,10,23,28,29] and has been widely used in research conducted in various hospital departments, proving to be a quality instrument for measuring this complex construct [19,[30][31][32][33][34][35]. Validations of the questionnaire in all countries indicated a one-factor structure, except for the Arabic version, which suggested the existence of two factors: "satisfaction with the care provided" and "satisfaction with the information provided" [29].…”
Section: Literature Reviewmentioning
confidence: 99%